Budget institutions and fiscal performance in Africa - Michael Bleaney (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2010)
This paper develops an index measuring the adequacy of the institutions, rules and procedures governing the budget process in 46 African countries, presenting the most comprehensive analysis of African budget institutions hitherto conducted. The index includes the three stages of the budget process: negotiation, legislative approval, and implementation. At each stage the quality of the budget process is measured along five criteria: centralization, rules and controls, sustainability and credibility, comprehensiveness, and transparency. A wide dispersion in institutional quality is found across the continent. Furthermore, an empirical analysis based on OLS estimations shows that better budget institutions are associated with lower public external debt and a higher primary budget balance.
Keywords: H61; H62; H63; E62; 330; Budget Institutions; Budget Systems; African Countries; Fiscal Policy; Öffentlicher Haushalt; Haushaltsverfahren; Institutionelle Infrastruktur; Finanzpolitik; Afrika